Application of the Six Sigma Method to Minimize Leaking in Pillow Pack Cooking Oil Packaging at PT. ABC - Alifiansyah Rizaldy Satya Putra; Moh. Jufriyanto; Efta Dhartikasari Priyana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
PT. ABC is a company that has a cooking oil production business. In order to remain competitive with similar companies, the quality of the product must be maintained and improved. One of the problems of PT. ABC is the existence of leakage in the pillow pack packaging. The Six Sigma method can be used to identify the triggers for the leaking. This community service activity provides suggestions for improving the pillow pack cooking oil packaging process so that the amount of leaking can be reduced. Proposals are prepared by identifying the packaging process with reference to the Six Sigma method assisted by several statistical tools (check sheets, stratification, Pareto diagrams as well as fishbone diagrams). It was found that the highest leakage occurred on the horizontal side of the pillow pack (55%). On the basis of these findings, the proposed improvements lead to making a machine repair schedule at certain hours and then carrying out maintenance on the filling machine.